Changes in CD4 Counts and Viral Load of HIV/AIDS Patients Before and After 6 Months of ARV Therapy at Banyumas Hospital : A Case Study - Dini Puspodewi; Widya Nur Islami; Hartika Aulia Putri; Mei Cahya Pangesti; Dwi Kusuma Ningsih; Linda Wijayanti; Sri Nursaptiwi (LPPM Universitas Abdurrab, 2025)
Human Immunodeficiency Virus (HIV) remains a major health challenge because the infection progressively weakens the immune system by reducing CD4 cell counts and increasing the risk of opportunistic infections such as pulmonary tuberculosis. Antiretroviral therapy (ART) is essential to suppress viral replication and support immune recovery. This study aims to describe the changes in CD4 counts and Viral Load in HIV/AIDS patients before and after six months of ART at Banyumas Regional Hospital. A descriptive case study approach was used, involving two male patients diagnosed with stage-3 HIV/AIDS accompanied by pulmonary TB. Data were obtained from medical records, including CD4 counts and Viral Load measurements taken before and after treatment. The results show an increase in CD4 levels in both patients. In the first case, CD4 increased from 9 cells/µL to 88 cells/µL, while in the second case, CD4 rose from 156 cells/µL to 533 cells/µL. Both patients also achieved a Viral Load of <40 copies/mL after six months of ART, indicating successful viral suppression. Overall, the findings demonstrate that ART contributed to meaningful immunological improvement and a substantial reduction in Viral Load. Consistent treatment adherence and regular monitoring remain essential to ensure optimal therapeutic outcomes.